Biogenesis and Function of Circular RNAs in Health and in Disease - Haddad, George; Lorenzen, Johan M. (Frontiers in Pharmacology, 2019)
Circular RNAs (circRNAs) are a class of noncoding RNA that were previously thought to be insignificant byproducts of splicing errors. However, recent advances in RNA sequencing confirmed the presence of circRNAs in multiple cell lines and across different species suggesting a functional role of this RNA species. CircRNAs arise from back-splicing events resulting in a circular RNA that is stable, specific and conserved. They can be generated from exons, exon-introns, or introns. CircRNAs have multifaceted functions. They are likely part of the competing endogenous RNA class. They can regulate gene expression by sponging microRNAs, binding proteins or they can be translated into a protein themselves. CircRNAs have been associated with health and disease, some with disease protective effects, some with disease promoting functions. The widespread expression and disease regulatory mechanisms endow circRNAs to be used as functional biomarkers and therapeutic targets for a variety of different disorders. In this concise article we provide an overview of the association of circRNAs with various diseases. In addition their role in maintaining physiological cellular homeostasis is discussed. We provide a summary on the fledgling body of literature on kidney-specific as well as cardiovascular circRNAs.